Description of embryo development in cassava = Descripción del desarrollo embrionario en yuca - Ramos, Lisette Natalia; Wedzony, Maria; Lentini, Zaida; Buitrago, María Eugenia; Tabares Z., Eddie; Vanegas, Freddy; Ceballos, Hernán (International Center for Tropical Agriculture, 2018)
This 16-minute video describes the protocol used for the preparation of sections for the histological analysis of cassava pistils of different ages after anthesis. Consolidated results after studying hundreds of samples, present a chronological description of embryo sac and the embryo appearance at different stages of development. Este video de 16 minutos describe el protocolo usado en la preparación de muestras para el estudio histológico de pistilos de yuca/mandioca a diferentes edades luego de la antesis. Resultados consolidados, después de analizar cientos de secciones, presentan una descripción cronológica de los diferentes estadios de desarrollo embrionario.